SKRINING FITOKIMIA INFUSA DAUN SUNGKAI (Peronema canescens Jack.) DENGAN METODE REAKSI WARNA - Rahmawati, Suci; Marliza, Marliza; Sari, Rose Intan Perma; Wirahmi, Nori; Oktoviani, Oktoviani; Sipriyadi, Sipriyadi (Jurnal Pharmacopoeia, 2023)
Sungkai (Peronema canescens Jack) was used traditionally as a medicine to help relieve fever, malaria and flu. In general, people was used sungkai leaves in the form as infusion. This study was aimed to screening of secondary metabolite of Sungkai leaf infusion using the color reaction method. The sample in this study was sungkai leaf that obtained from Bengkulu city. The infusion was obtained by boiling 10 gram of sungkai leaf simplicia with 100 ml of distilled water for 15 minutes at 90 0C until a concentration of 10% (w/v) was obtained. Secondary metabolite screening was carried out using the color reaction method to identify alkaloids, flavonoids, saponins, tannins and steroids. Phytochemical screening using specific reagents with the test was repeated three times. The results were showed that sungkai leaves infusion was positive in alkaloid test as evidenced by the presence of white precipitate with Mayer reagent, brown precipitate with Wagner reagent, and orange precipitate with Dragendorff reagent. Positive results were also shown in flavonoid, saponin and tannin tests. While, negative result was seen in steroid test using Liebermann Burchard reagent. In this study it can be concluded that sungkai leaf infusion positively contains alkaloids, flavonoids, saponins and tannins.